VOLATILITAS RETURN SAHAM DI INDONESIA : POLA DAN PERBANDINGAN DENGAN MALAYSA DAN SINGAPURA - Oviar Candra Bumi (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2013)
During the last decade, volatility issues have been common tofics for stock market partisipants in line with increasing financial market liberalization, Why does volatility matter if excesive return volatility happened, it endangers stock market by blurring the usefulness of stock prices as a fair representative of company value (karolyi,2001). This paper will elaborate the pattern of return volatility in indonesia, especially in periode before and during the world financial crisis, malaysa and singapore, were taken into account for a comparison , By using student-t EGARCH the existence of the asymmetric effect on return volatility upon the market shock was well document, where volatility was more influenced by negative shocks rather than positive shocks. Its was also found that during the crisis, the shocks magnitude in indonesia was greater, as compared to that of malaysia and Singapore, nonetheless, in term of persistence, indonesia was in between malaysia and singapore.